Cancer Nanomedicine and Immune System—Interactions and Challenges - Ahmad, Suhana; Idris, Ros Akmal Mohd; Wan Hanaffi, Wan Nurhidayah; Perumal, Komathi; Boer, Jennifer C.; Plebanski, Magdalena; Jaafar, Juhana; Lim, Jit Kang; Mohamud, Rohimah (Frontiers in Nanotechnology, 2021)
Nanoparticles have tremendous therapeutic potential in the treatment of cancer as they increase drug delivery, attenuate drug toxicity and protect drug from rapid clearance. Since Doxil®, the first FDA-approved nanomedicine, several other cancer nanomedicine have been approved and successfully increased the efficacy over their free drug counterparts. Although their mechanisms of action are well established, their effects towards our immune system, particularly in tumor microenvironment (TME), still warrant more investigations. Herein, we review the interactions between approved cancer nanomedicine with the TME immunology. We also discussed the challenges need to be addressed for full clinical potential of ongoing cancer nanomedicine despite the encouraging preclinical data.